Preparation and electro-catalysis application of transition metal ion modified bimetallic MXene

By adjusting the type and concentration of metal salt solution, the metal ion intercalation modification of bimetallic MXene has been solved, and the lack of modification of bimetallic MXene in the prior art has been optimized, and its surface chemical properties and electrochemical properties have been optimized, which has significantly improved its application effect in energy storage and catalytic reactions.

CN119800411AActive Publication Date: 2025-04-11CHINA THREE GORGES UNIV

Patent Information

Application Number
CN202510145921.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-11
Estimated Expiration
2045-02-10

AI Technical Summary

Technical Problem

The existing technology has not fully studied the modification effect of transition metal ion intercalation on bimetallic MXene, especially how to optimize its surface chemical properties and electrochemical properties by adjusting the types and concentration of metal salts.

Method used

By adjusting the type, concentration and intercalation conditions of the metal salt solution, the metal ion intercalation strategy is used to modify the bimetallic MXene to form stable chemical bonding to improve its surface conductivity, stability and catalytic activity.

Benefits of technology

It significantly improves the electrochemical performance of bimetallic MXene, such as high specific capacity, excellent conductivity, and high catalytic activity, and is suitable for supercapacitors, batteries, catalysts and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800411A_ABST
    Figure CN119800411A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of transition metal ion modified bimetallic MXene, which comprises the following steps: preparing different metal ions (Co < 2 + >, Ni < 2 + > and Mn < 2 + >) and Mo2TiC2Tx materials (marked as Mo2TiC2Tx-M) with different intercalation concentrations through electrostatic interaction, and carrying out detailed characterization and analysis on the Mo2TiC2Tx materials to explore the feasibility of MXene material modification. By analyzing the phase and morphology of the prepared sample, the transition metal ion intercalation enables the structure of Mo2TiC2Tx to become looser, and meanwhile, the interlayer spacing of Mo2TiC2Tx is remarkably increased. By introducing metal ions, a new metal bond can be formed, and electrons can be efficiently transferred. The research on the electrochemical performance of the material finds that the bimetallic MXene of the metal ion intercalation has excellent electro-catalytic hydrogen evolution performance and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a transition metal ion modified bimetallic MXene, and specifically to modifying the bimetallic MXene using a transition metal salt solution, thereby improving its surface chemical properties and electrochemical performance, and is widely used in energy storage, catalytic reactions, supercapacitors and other fields. Background Art

[0002] MXene is a class of two-dimensional materials composed of transition metal carbides, nitrides or carbonitrides, usually obtained from layered precursors by chemical etching methods. This material has excellent conductivity, high specific surface area, adjustable surface chemical properties and strong mechanical strength, so it has a wide range of applications in energy storage, catalysis, sensors and supercapacitors. However, although MXene materials themselves have good electrochemical properties and catalytic activity, there is still a need to further improve their conductivity, stability and catalytic activity in practical applications.

[0003] In recent years, researchers have proposed to modify the surface of MXene by metal ion intercalation strategy to improve its electrochemical performance and catalytic activity. Metal ion intercalation can be achieved by introducing transition metal ions (such as Ni 2+ 、Co 2+ , Cu 2+ Intercalation of transition metal ions such as nickel and cobalt not only improves the electrical conductivity of MXene, but also improves its performance in electrochemical devices such as batteries and supercapacitors.

[0004] As a new modified form of MXene material, bimetallic MXene can achieve synergistic enhancement of material performance by introducing two different transition metal elements (such as Ni and Co, Ni and Cu, etc.). Bimetallic MXene not only has richer structural and surface chemical properties than monometallic MXene, but also provides more active sites and higher electrochemical activity, which makes it have a wider application prospect in the fields of electrochemical energy storage and catalytic reactions.

[0005] Although studies have shown that metal ion intercalation can effectively modify MXene, existing technologies mainly focus on the effect of metal ion intercalation on single metal MXene, and the modification effect of transition metal ion intercalation on bimetallic MXene has not been fully studied. In particular, how to achieve efficient modification of bimetallic MXene by adjusting the type and concentration of metal salts has not been effectively solved. Therefore, how to adjust the surface chemical properties and electrochemical performance of bimetallic MXene by optimizing the metal ion intercalation process is an important challenge in the current technical field.

[0006] The present invention provides a method for efficiently modifying bimetallic MXene by adjusting the type, concentration and intercalation conditions of the metal salt solution to optimize its performance, especially its advantages in electrochemical energy storage and catalytic applications. Summary of the invention

[0007] The present invention provides a method for preparing a transition metal ion modified bimetallic MXene, which aims to adjust the surface chemical characteristics and electrochemical performance of bimetallic MXene by controlling the type and concentration of metal salts, thereby improving its application effect in energy storage and catalytic reactions. The method of the present invention comprises reacting a MXene material with a transition metal salt solution, wherein the transition metal ions form a stable chemical bond with the surface of the MXene material through ion exchange or intercalation, thereby improving the surface conductivity, stability and catalytic activity of the MXene. The method is simple to operate, has strong adaptability, and can optimize its performance without changing the basic structure of the MXene.

[0008] Through the preparation method of the present invention, the obtained transition metal modified bimetallic MXene exhibits significantly improved electrochemical properties, such as high specific capacity, excellent electrical conductivity, high catalytic activity, etc., and is particularly suitable for supercapacitors, batteries, catalysts and other fields.

[0009] The technical solution of the present invention is as follows: a transition metal ion-modified bimetallic MXene is used as a HER electrode material, and the material is prepared by transition metal ion intercalated layered bimetallic MXene.

[0010] A method for preparing a transition metal ion modified bimetallic MXene, the method comprising the following steps: (1) Add Mo2TiAlC2 powder to a concentrated HCl mixed solution containing NaF and stir to perform etching reaction. After etching, centrifuge, wash, and vacuum dry to obtain Mo2TiC2T x ; In some embodiments, during the washing process in step (1), the product is washed several times with DI water by centrifugation until the pH of the supernatant is greater than or equal to 6, such as 6-7.5.

[0011] (2) Mo2TiC2T x The monolayer Mo2TiC2T was dispersed in a glass bottle filled with water, degassed with argon, and then sealed and ultrasonically peeled at room temperature to obtain a single layer of Mo2TiC2T x ; In some embodiments, the water in step (2) is DI water, and the ultrasonic stripping time is not less than 8 hours, generally 8-12 hours.

[0012] (3) Single-layer Mo2TiC2T x Disperse in a glass bottle filled with water, add transition metal salt solution of appropriate concentration, and introduce inert protective gas, seal and stir to perform intercalation reaction to obtain intercalation sample Mo2TiC2T x -M; (4) The intercalated sample Mo2TiC2TT x -M was centrifuged, washed and vacuum dried to obtain the transition metal ion modified bimetallic MXene product.

[0013] The concentration of NaF in step (1) is 0.3-1 g / mL; the mass concentration of concentrated HCl is 36-38%.

[0014] The etching reaction temperature in step (1) is 70 ± 5 °C, and the etching reaction time is 2-7 days.

[0015] Mo2TiC2T in step (3) x The concentration of the dispersion is 0.5-5 mg mL -1 .

[0016] In some embodiments, Mo2TiC2T x The optimal concentration of the dispersion is 1 mg mL -1 .

[0017] The transition metal salt in step (3) is any one of acetate, nitrate, sulfate and halide of nickel, cobalt, manganese, iron and copper; the concentration of the transition metal salt solution is 0.1-1 mM.

[0018] In some embodiments, the optimal metal salt is nickel acetate (Ni(OAc)2); the optimal concentration of nickel acetate (Ni(OAc)2) in step (3) is 1 mM.

[0019] The addition rate of the transition metal salt solution in step (3) is controlled at 0.5-1 mL / min.

[0020] The inert gas described in step (3) is argon and nitrogen; the flow rate of the inert protective gas is 20-50 mL / min.

[0021] The intercalation reaction temperature in step (3) is 40-80°C, the intercalation reaction time is 8-48 h, and the intercalation reaction stirring speed is 200-800 rpm.

[0022] In some embodiments, the optimal intercalation temperature is 60° C., the optimal intercalation time is 24 h, and the optimal stirring speed is 500 rpm.

[0023] The prepared transition metal ion-modified bimetallic MXene has a flaky structure with an increased interlayer spacing. The transition metal intercalation makes the edge of the material present an irregular shape, providing it with more active sites.

[0024] Another technical solution of the present invention is to use a transition metal ion-modified bimetallic MXene in electrocatalytic hydrogen evolution (HER).

[0025] The transition metal ion intercalated Mo2TiC2T x After basic characterization of the material, the electrocatalytic hydrogen evolution performance was tested. The specific method is as follows: Mo2TiC2T x -M was prepared into a uniform electrode dispersion and then drop-coated on the carbon cloth. After drying, the catalytic working electrode was successfully prepared. The catalyst loading was 0.5 mg cm -2 The reference electrode is Ag / AgCl electrode, the counter electrode is platinum wire, and the electrolyte is 0.5 M H2SO4. In order to eliminate the influence of Pt on the hydrogen evolution reaction, an H-type electrolytic cell was used for electrochemical testing. x -1 mM Ni 2+ It exhibits excellent electrocatalytic hydrogen evolution performance and has ultra-long stability.

[0026] The beneficial effects of the present invention are as follows: (1) The synthesis method is simple and efficient: The present invention adopts a metal ion intercalation strategy and successfully realizes Mo2TiC2T through liquid phase etching and subsequent intercalation reaction. x -M material preparation. The synthesis process is simple to operate, has low equipment requirements, and is suitable for large-scale production.

[0027] (2) Optimized structural design: intercalated metal ions (such as Ni 2+ 、Co 2+ , Mn 2+ ) significantly expanded the Mo2TiC2T x The interlayer spacing of the nanostructured carbon nanotubes increases the surface area of ​​the nanostructured carbon nanotubes, providing more active sites for electrocatalytic reactions and enhancing the contact efficiency with the electrolyte.

[0028] (3) Improving electronic structure and conductivity: Metal ion intercalation optimizes the electronic structure of the material, promotes the redistribution of interfacial charge, significantly reduces the charge transfer resistance (Rct), increases the charge transfer rate, and provides kinetic advantages for the electrocatalytic hydrogen evolution reaction (HER).

[0029] (4) Excellent catalytic performance: Thanks to the structural optimization and electronic regulation of metal ion intercalation, Mo2TiC2T x -Ni 2+ The overpotential required at 10 mA cm⁻² is only 93 mV, and the Tafel slope is 80 mV·dec -1 , which is significantly better than the unintercalated materials and other metal intercalated samples (such as Co 2+ and Mn 2+ ).

[0030] (5) Excellent long-term stability: at 10 mA cm -2 After 700 hours of long-term stability testing at current density, Mo2TiC2T x -Ni 2+ The catalyst still maintains good structure and electrocatalytic performance, with voltage fluctuation only within 100 mV, showing excellent cycle stability.

[0031] (6) Wide application potential: The metal ion intercalation strategy of the present invention is applicable to the performance optimization of other MXene materials. It not only exhibits excellent performance in the hydrogen evolution reaction (HER), but can also be widely used in other electrocatalytic reactions and energy storage fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The different concentrations of Ni synthesized in Example 1 + Intercalated Mo2TiC2T x XRD schematic diagram of .

[0033] Figure 2 Mo2TiC2T synthesized in Example 1 x –Ni 2+ Scanning electron microscope image of .

[0034] Figure 3 Mo2TiC2T synthesized in Example 1 x -Ni 2+ Transmission electron microscopy image of .

[0035] Figure 4 Mo2TiC2T synthesized in Example 1, Example 2 and Example 3 x -LSV comparison chart of M.

[0036] Figure 5The concentration of Ni synthesized in Example 1 is + Intercalated Mo2TiC2T x LSV comparison chart. DETAILED DESCRIPTION

[0037] The present invention is further described below with reference to embodiments, but the scope of protection claimed by the present invention is not limited to the scope described in the embodiments.

[0038] Single-layer Mo2TiC2T x Preparation: (1) 0.5 g of Mo2TiAlC2 powder was slowly added to a mixed solution of concentrated HCl (36-38%) containing NaF (0.5 g / mL), and then stirred at a certain temperature for several days. After etching, the product was washed several times with DI water by centrifugation until the pH of the supernatant was 6.5. Finally, the obtained black sample was vacuum dried for several hours, and Mo2TiC2T x .

[0039] (2) Weigh an appropriate amount of etched Mo2TiC2T x The sample was dispersed in a glass bottle filled with DI water, and argon was continuously introduced for degassing. It was sealed and ultrasonically peeled at room temperature for 8 h to obtain a single layer of Mo2TiC2T x .

[0040] Example 1 (1 mM Ni 2+ Intercalation, Mo2TiC2T x -Ni 2+ Preparation of 20 mg of single-layer Mo2TiC2T x Dispersed into 20 mL of 1 mM nickel acetate (Ni(OAc)2) solution, the inert protective gas argon was continuously introduced for 15 minutes, the glass bottle was sealed, and stirred at 60 °C and 500 rpm for 24 h to obtain the intercalated sample Mo2TiC2T x -Ni 2+ The intercalated powder samples were collected by centrifugation at 5000 rpm and washed several times with deionized water to obtain the intercalated Mo2TiC2T x -Ni 2+ Sample. Mo2TiC2T x -Ni 2+ At 10 mA cm -2 The overpotential at this current density is 92 mV.

[0041] XRD shows that different concentrations of Ni 2+ Insertion of Mo2TiC2T xThe expansion of the interlayer spacing was not significantly affected. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analysis showed that after metal ion intercalation, Mo2TiC2T x -Ni 2+ The microscopic morphology has changed significantly. Figure 3 The SEM images show that after intercalation, Mo2TiC2T x The tight layered structure becomes loose, forming a lamellar structure with increased interlayer spacing. Figure 4 TEM analysis further confirmed this result. x The original layered structure of Ni 2+ Intercalation gives the material an irregular shape at the edge, providing it with more active sites. Figure 5 The LSV curves of different transition metal salt ions show that Ni 2+ Intercalated Mo2TiC2T x -Ni 2+ Possesses the smallest HER overpotential (92 mV).

[0042] Example 2 (1 mM Co 2+ Intercalation, Mo2TiC2T x -Co 2+ Preparation of Changing the above transition metal salt to cobalt acetate (Co(OAc)2), and the other experimental conditions are the same as those in Experimental Example 1, Mo2TiC2T x -Co 2+ .Mo2TiC2T x -Co 2+ At 10 mA cm -2 The overpotential at this current density is 282 mV.

[0043] Example 3 (1 mM Mn 2+ Intercalation, Mo2TiC2T x -Mn 2+ Preparation of Changing the above transition metal salt to cobalt acetate (Mn(OAc)2), and the other experimental conditions are the same as those in Experimental Example 1, Mo2TiC2T x -Mn 2+ .Mo2TiC2T x -Mn 2+ At 10 mA cm -2 The overpotential at this current density is 186 mV.

[0044] Example 4 (0.1 mM Ni 2+ Intercalation, Mo2TiC2T x -Ni2+ Preparation of Changing the concentration of the nickel acetate (Ni(OAc)2) dispersion to 0.1 mM, and the other experimental conditions are the same as those in Experimental Example 1, Mo2TiC2T x -Ni 2+ .Mo2TiC2T x -0.1 mM Ni 2+ At 10 mA cm -2 The overpotential at this current density is 165 mV.

[0045] Example 5 (10 mM Ni 2+ Intercalation, Mo2TiC2T x -Ni 2+ Preparation of Changing the concentration of the nickel acetate (Ni(OAc)2) dispersion to 10 mM, and the other experimental conditions are the same as those in Experimental Example 1, Mo2TiC2T x -Ni 2+ .Mo2TiC2T x -10 mM Ni 2+ At 10 mA cm -2 The overpotential at this current density is 170 mV.

[0046] Example 6 (NaF etching of Mo2TiC2T x ) 0.5 g of Mo2TiAlC2 powder was slowly added to a mixed solution of concentrated HCl (36-38%) containing NaF (0.5 g / ml), and then stirred at a certain temperature for several days. After etching, the product was washed several times with DI water by centrifugation until the pH of the supernatant was 6.5. Finally, the resulting black sample was vacuum dried for several hours, and Mo2TiC2T was finally collected. x Weigh an appropriate amount of etched Mo2TiC2T x The sample was dispersed in a glass bottle filled with DI water, and argon was continuously introduced for degassing. It was sealed and ultrasonically peeled at room temperature for more than 8 h to obtain a single layer of Mo2TiC2T x .Mo2TiC2T x At 10 mA cm -2 The overpotential at this current density is 328 mV.

[0047] Example 7 (LiF Etching Mo2TiC2T x ) 0.5 g of Mo2TiAlC2 powder was slowly added to a mixed solution of concentrated HCl (36-38%) containing LiF, with a LiF concentration of 0.5 g / ml, and then stirred at a certain temperature for several days. After etching, the product was washed several times with DI water by centrifugation until the pH of the supernatant was 6.5. Finally, the resulting black sample was vacuum dried for several hours, and Mo2TiC2T was finally collected. x Weigh an appropriate amount of etched Mo2TiC2T x The sample was dispersed in a glass bottle filled with DI water, and argon was continuously introduced for degassing. It was sealed and ultrasonically peeled at room temperature for more than 8 h to obtain a single layer of Mo2TiC2T x Mo2TiC2T obtained by LiF etching x At 10 mA cm -2 The overpotential at this current density is 410 mV.

[0048] The present invention designs and synthesizes a series of Mo2TiC2Tx-M electrocatalysts by a simple and mild metal ion intercalation method. The metal ions are uniformly distributed in the Mo2TiC2Tx x The interlayer and surface of MXene significantly improve its electrocatalytic hydrogen evolution performance in acidic electrolytes. Metal ion intercalation effectively expands the interlayer spacing of MXene, making its layered structure looser and presenting a flaky morphology, which is beneficial to increase the contact area between the catalyst and the electrolyte and provide more reactive sites. In addition, metal ions can be stably anchored in Mo2TiC2T x Strong metal bonds are formed on MXene, promoting efficient electron transfer, thereby improving catalytic performance. By adjusting the type and concentration of metal ions, the hydrogen evolution activity and stability of the catalyst can be further optimized. This interlayer space regulation strategy provides new ideas and possibilities for the application of MXenes in the field of electrocatalysis.

[0049] The above-mentioned embodiments are only preferred technical solutions of the present invention and should not be regarded as limitations of the present invention. The embodiments and features in the embodiments of the present application can be arbitrarily combined with each other without conflict. The protection scope of the present invention shall be the technical solutions recorded in the claims, including the equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.

Claims

1. A method for preparing a transition metal ion modified bimetallic MXene, characterized in that: The synthesis method comprises the following steps: (1) Add Mo2TiAlC2 powder to a concentrated HCl mixed solution containing NaF and stir to perform etching reaction. After etching, centrifuge, wash, and vacuum dry to obtain Mo2TiC2T x ; (2) Mo2TiC2T x The monolayer Mo2TiC2T was dispersed in a glass bottle filled with water, degassed with argon, and then sealed and ultrasonically peeled at room temperature to obtain a single layer of Mo2TiC2T x ; (3) Single-layer Mo2TiC2T x Disperse in a glass bottle filled with water, add transition metal salt solution of appropriate concentration, and introduce inert protective gas, seal and stir to perform intercalation reaction to obtain intercalation sample Mo2TiC2T x -M; (4) The intercalated sample Mo2TiC2T x -M was centrifuged, washed and vacuum dried to obtain the transition metal ion modified bimetallic MXene product.

2. The method for preparing a transition metal ion modified bimetallic MXene according to claim 1, characterized in that: The concentration of NaF in step (1) is 0.3-1 g / mL; the mass concentration of concentrated HCl is 36-38%.

3. The method for preparing the transition metal ion modified bimetallic MXene according to claim 1, characterized in that: The etching reaction temperature in step (1) is 70 ± 5 °C, and the etching reaction time is 2-7 days.

4. The method for preparing the transition metal ion modified bimetallic MXene according to claim 1, characterized in that: The Mo2TiC2T in step (3) x The concentration of the dispersion is 0.5-5 mg mL -1 .

5. The method for preparing the transition metal ion modified bimetallic MXene according to claim 1, characterized in that: The transition metal salt described in step (3) is acetate, nitrate, Any one of sulfate and halide; the concentration of the transition metal salt solution is 0.1-1mM.

6. The method for preparing a transition metal ion modified bimetallic MXene according to claim 1, characterized in that: The addition rate of the transition metal salt solution in step (3) is controlled at 0.5-1 mL / min.

7. The method for preparing a transition metal ion modified bimetallic MXene according to claim 1, characterized in that: The inert gas described in step (3) is argon and nitrogen; the flow rate of the inert protective gas is 20-50 mL / min.

8. The method for preparing a transition metal ion modified bimetallic MXene according to claim 1, characterized in that: The intercalation reaction temperature in step (3) is 40-80°C, the intercalation reaction time is 8-48 h, and the intercalation reaction stirring speed is 200-800 rpm.

9. The method for preparing a transition metal ion modified bimetallic MXene according to any one of claims 1 to 8, characterized in that: The prepared transition metal ion-modified bimetallic MXene has a flaky structure with an increased interlayer spacing. The transition metal intercalation makes the edge of the material present an irregular shape, providing it with more active sites.

10. Use of the transition metal ion modified bimetallic MXene prepared according to the method according to any one of claims 1 to 9 as an electrocatalytic material for hydrogen evolution.

Citation Information

Patent Citations

  • Preparation method of MXene composite material for supercapacitor electrode material and MXene composite material

    CN110803702A

  • Preparation method and application of two-dimensional MXene / iron-cobalt-based composite catalytic material

    CN111659431A

Cited By

  • Method for regulating and controlling interlayer spacing and superconducting performance of Mo2C MXene through transition metal ion intercalation

    CN121317752A